PENGEMASAN BAHAN AJAR TARI TAPA-TAPA DALAM BENTUK AUDIO VISUAL (VCD) UNTUK SISWA KELAS X SEKOLAH MENENGAH ATAS DI SUMATERA UTARA - Elma Sema Putri Siregar (Gesture: Jurnal Seni Tari, 2020)
ABSTRACTThis study aims to describe the packaging of teaching materials on the material of Appreciation and Expression of the Tapa-tapa Dance through audio visual to be taught to students of class X of High Schools in North Sumatra. In addition, it describes the steps and results in making Tapa-tapa Dance packaging through audio visual to be taught to high school students in North Sumatra. The theories used are Setyosari's (2015) packaging theory, namely packaging steps which include planning, compilation, production, and evaluation. The theory of teaching materials Prastowo (2015) is a teaching material that is arranged systematically and used for the learning process in the form of audio visual. The method used in this study is a qualitative research method. The instrument used to test the feasibility of audio visual teaching material (VCD) is to use the Audio Visual Product Validation Test (VCD) questionnaire and the Material Validation Test Questionnaire, this questionnaire consists of aspects of assessment which are based on competency standards. This research resulted in an audio visual teaching material product VCD for Tapa-tapa dance material. Starting from (1) Planning by making teaching materials, selecting dancers, determining the location of taking photos and videos of products, and preparing facilities and infrastructure, (2) Preparation, where all teaching materials for KD 3 appreciation and KD 4 expressions covering background behind the Tapa-tapa dance, the Tapa-tapa dance function, the basic movements of the Tapa-tapa dance, cosmetology, fashion, musical instruments, tutorials and video performances of the Tapa-tapa dance performance that can be used as teaching material in dance learning, (3) Production is editing of images and sound results using Wondershare Filmore, (4) Evaluation, conducted by 2 validators for material validation and 1 validator for audio visual validation (VCD) by providing a validation questionnaire. In the validation stage, the results of validation by material experts with a score of 4.6 and validation by audio visual product (VCD) experts with a score of 4.4. From the score the product of teaching material in the form of audio visual (VCD) got a very good category applied to students of class X of High School in North Sumatra. Keywords: Packaging, Teaching Materials, Audio Visual (VCD) ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan pengemasan bahan ajar pada materi Apresiasi dan Ekspresi Tari Tapa-tapa melalui audio visual untuk diajarkan kepada siswa kelas X Sekolah Menengah Atas di Sumatera Utara. Selain itu mendeskripsikan langkah-langkah dan hasil dalam pembuatan pengemasan Tari Tapa-tapa melalui audio visual untuk dapat diajarkan kepada siswa Sekolah Menengah Atas di Sumatera Utara. Teori-teori yang digunakan adalah teori pengemasan Setyosari (2015) yaitu langkah-langkah pengemasan yang meliputi perencanaan, penyusunan, produksi, dan evaluasi. Teori bahan ajar Prastowo (2015) yaitu materi ajar yang disusun sistematis dan digunakan untuk proses pembelajaran dalam bentuk audio visual. Metode yang digunakan dalam penelitian ini adalah metode penelitian kualitatif.  Instrumen yang digunakan untuk menguji kelayakan bahan ajar audio visual (VCD) adalah dengan menggunakan angket Uji Validasi Produk Audio Visual (VCD) dan Angket Uji Validasi Materi, angket ini terdiri dari aspek penilaian yaitu berdasarkan standar kompetensi. Penelitian ini menghasilkan suatu produk bahan ajar audio visual VCD materi tari Tapa-tapa. Dimulai dari (1) Perencanaan dengan pembuatan materi bahan ajar, pemilihan penari, penetapan lokasi pengambilan foto dan video produk, serta penyiapan sarana dan prasarana, (2) Penyusunan, dimana semua materi bahan ajar kegiatan  KD 3 apresiasi dan KD 4 ekspresi yg meliputi latar belakang tari Tapa-tapa, fungsi tari Tapa-tapa, gerak dasar tari Tapa-tapa, tata rias, tata busana, alat musik, tutorial serta penampilan video pertunjukan tari Tapa-tapa yang dapat digunakan sebagai bahan ajar pada pembelajaran tari, (3) Produksi yakni penyuntingan hasil gambar dan suara dengan menggunakan Wondershare Filmore, (4) Evaluasi, dilakukan oleh 2 validator untuk validasi materi dan 1 validator untuk validasi audio visual (VCD) dengan cara pemberian angket validasi. Pada tahap validasi, dengan hasil validasi oleh ahli materi dengan skor 4,6 dan validasi oleh ahli produk audio visual (VCD) dengan skor 4,4. Dari skor tersebut produk bahan ajar dalam bentuk audio visual (VCD) mendapat kategori sangat baik diterapkan untuk siswa kelas X Sekolah Menengah Atas di Sumatera Utara.Kata Kunci: Pengemasan, Bahan Ajar, Audio Visual (VCD)